A method for measuring pressure-area isotherms of insoluble surfactant monolayers. (November 2017) - Ponce-Torres, A.
Highlights: A method for obtaining pressure-area isotherms of Langmuir monolayers is proposed. It relies on the fitting of part of the experimental data to an equation of state. It removes the need of knowing the initial amount of surfactant deposited. Validation has been carried out by taking measured experimental isotherms. Abstract: A simple method for measuring pressure-area isotherms of insoluble surfactant monolayers is proposed. It can be seen as a variant of the ADSA-PD/CSD (Axisymmetric Drop Shape Analysis-Pendant Drop/Constrained Sessile Drop) film balance technique, where both the surface pressure and area per surfactant molecule are measured in the course of the experiment. In the proposed method, the measurement of this latter quantity is substituted by a straightforward fitting of an equation of state to the surface pressure values. In this way, one eliminates the main source of error of the ADSA-PD/CSD technique: the accurate determination of the small amount of surfactant deposited on the interface. The comparison between previous experimental results and those obtained with this approach shows remarkable agreement (the relative deviations in the area per surfactant molecule are of the order of 1%).